Safer Tractor Operations for Emergency and Rescue Personnel - Carol J. Lehtola; Dave Hill; Charles M. Brown (EDIS)
This publication is intended to give emergency and resuce workers some background in the appropriate uses of tractors, a common vehicle in many contexts, especially agriculture, construction, and landscaping/grounds maintenance. This document is CIR 1253, one of a series of the Agricultural and Biological Engineering Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published April 2003.